Automated Heuristic Evaluator - Ahmad, Wan Fatimah Wan; Sarlan, Aliza; Juanis, Ezekiel A/L (Journal of Informatics and Mathematical Sciences, 2016)
Website testing becomes more challenging nowadays as numbers of websites are growing rapidly. Currently, most websites testing are still being conducted manually. Also, website testing consumes substantial amount of time that leads to client frustration and loosen up the bond between two parties. Therefore, an automated website testing is vital for Information Technology projects in order to carry out large number of tests in shorter period of time. This paper presents a web based validation system for website testing called as an Automated Heuristic Evaluator (AHE). AHE entails the features of checking invalid hyperlinks, visual clarity checking, readability scores and mobile friendly test of webpages. AHE is developed using PHP, JScript and HTML language integrating four selected principles of 12 Heuristic Principles. A user acceptance study has also been conducted with 7 software testers. The results found promising result from AHE for an effective software testing in future.